Motorcycle helmet: Part III. Manufacturing issues - Shuaeib, F. M.; Hamouda, A. M.S.; Hamdan, M. M.; Radin Umar, R. S.; Hashmi, M. S.J. (Elsevier B.V., 2002)
In this paper the motorcycle helmet manufacturing aspects are reviewed. Firstly the details of shell manufacturing are presented. Both the thermoplastic and the composite shell manufacturing techniques are presented with specific mentioning of the advantages and disadvantages to each type from the manufacturing point of view. Secondly, the manufacturing methods of different foam types used as motorcycle helmet liners are described and their characteristics are discussed. © 2002 Published by Elsevier Science B.V.